Remallado de terrenos multirresolución - Cifuentes, María Virginia (2007)
This paper proposes a new methodology for the multiresolution visualization of earth’s topography defined by many adjacent real topographical models. The strategy refines progressively the model subdividing it into rectangular triangles, building a binary hierarchy generated by the progressive refining of the model, using the error indicator. It combines the observer location, the local curvature of the zone and the height fields and the triangle size put before. The triangulation applies refining and triangle grouping processes, adding or deleting detail to the representation.\nWe also apply previously developed ideas to real elevation digital models.